2013
DOI: 10.1080/15222055.2013.806383
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of SLICE (0.2% Emamectin Benzoate) Administered in Feed to Fingerling Rainbow Trout

Abstract: SLICE (0.2% emamectin benzoate [EB]) is an in‐feed treatment that has been shown to be effective and safe for controlling infestations of several ectoparasitic crustacean copepods and branchiurans in a variety of seawater‐ and freshwater‐reared fishes. Although the safety of EB (in a pre‐SLICE formulation) for use with seawater‐reared Rainbow Trout Oncorhynchus mykiss has been demonstrated, the safety of SLICE for freshwater‐reared Rainbow Trout has not. Consequently, we conducted a trial to evaluate the safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Considering the results, the differences between weight gains were not found to be significant (p > 0:05) and which is supporting the findings of Kilercioglu et al [24] where rainbow trout was administered at 50 μg EB kg -1 fish daily for 7, 14, and 21 days. After thorough investigation, we have come to end that no augmentation of growth in EB fed fish groups compared to control fish after 21 days of feeding which corroborate with earlier studies in rainbow trout and Atlantic salmon reported by few distinguished authors [20,25]. In addition to it, Siavash et al [26] also found that there was no mortality, or any difference in body weight and length between the controls and treated fish when rainbow trout was treated with another closely related drug i.e., ivermectin at 100 μg kg -1 intraperitoneal (IP) injections.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the results, the differences between weight gains were not found to be significant (p > 0:05) and which is supporting the findings of Kilercioglu et al [24] where rainbow trout was administered at 50 μg EB kg -1 fish daily for 7, 14, and 21 days. After thorough investigation, we have come to end that no augmentation of growth in EB fed fish groups compared to control fish after 21 days of feeding which corroborate with earlier studies in rainbow trout and Atlantic salmon reported by few distinguished authors [20,25]. In addition to it, Siavash et al [26] also found that there was no mortality, or any difference in body weight and length between the controls and treated fish when rainbow trout was treated with another closely related drug i.e., ivermectin at 100 μg kg -1 intraperitoneal (IP) injections.…”
Section: Discussionsupporting
confidence: 89%
“…The oating pelleted diets lasting in the tank 60 min after each feeding were siphoned into a pre-weighed vessel, dried overnight, and weighed. The feeding behaviour based on the feed consumed by the sh was noted daily and given numerical scores on a vepoint scale (Bowker et al 2013). The mortalities, sh behavioural changes like lethargy, aggressive and subdued feeding, position in the water column, equilibrium loss, uncharacteristic pigmentation or discolouration, gasping for air, ashing, hyperactivity, and other gross and dermal lesions were observed daily.…”
Section: Experimental Design and Dose Administrationmentioning
confidence: 99%
“…The histopathological changes in different organs of EB-dosed O. niloticus were evaluated based on the severity in comparison with control. The major changes were identi ed and given a qualitative assessment score using an ordinal scale, according to the percentage alteration of the tissue due to damages from its normal architecture (Bowker et al 2013). The investigational protocols ful lled the ethical guidelines including observance of the legal requirements of India (CPCSEA 2021).…”
Section: Histopathologymentioning
confidence: 99%
“…Emamectin benzoate is a compound that has safety data for the same species in both freshwater and salt water. In freshwater-held Rainbow Trout, no mortalities or signs of toxicity were observed after 14 d of oral treatment at a rate of 150 μg•kg body weight (BW) −1 •d −1 (3× the recommended dose and 2× the recommended treatment duration; Bowker et al 2013). In saltwater-held Rainbow Trout that were fed at 0, 100, 250, and 500 μg•kg BW −1 •d −1 (equivalent to 0, 2, 5, and 10× the recommended dose rate for treatment of sea lice Lepeophtheirus salmonis) for 7 d, there were no mortalities during the treatment or posttreatment periods (Roy et al 2000).…”
Section: Target Animal Safetymentioning
confidence: 99%